Habitat preferences and spatial distribution of larvae of Lipara Meigen, 1830 (Diptera: chloropidae) and associated entomofauna in galls - Anna Janicka; Edyta BuczyŃska; Ewa Szczuka; Adam Tarkowski; Paweł BuczyŃski (The European Zoological Journal)
Flies of the genus Lipara form galls in the apical part of the blades of the common reed Phragmites australis. Research on their occurrence was conducted in south-eastern Poland. All four species occurring in Poland were recorded. The diversity of their assemblages in particular habitats is described and their environmental drivers are indicated. Significant differences were found between the assemblages of Lipara larvae in reed beds in four habitats (meadows, forests, fens, and the littoral zone of water bodies) and the habitat preferences of the species are indicated. The spatial distribution of these species within reed beds was examined and no significant differentiation was found. The occurrence of other insects in Lipara-induced galls was preliminarily described, and it was found that they are common and highly diversified. Other Chloropidae (Cryptonevra sp.; Incertella sp.) were the most frequent and numerous, and only their occurrence was correlated with the occurrence of some Lipara species. The data presented in this study supplement and partially revise the previous knowledge of the ecology of Lipara spp. and their relationship with Phragmites australis. The study also has application potential in the control of pests of reed as a crop plant or in the control of reed as a weed.